2007
DOI: 10.1158/0008-5472.can-06-4061
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Influences for Mutation Induction Curves after Exposure to DNA-Reactive Carcinogens

Abstract: A mechanistic understanding of carcinogenic genotoxicity is necessary to determine consequences of chemical exposure on human populations and improve health risk assessments. Currently, linear dose-responses are assumed for DNA reactive compounds, ignoring cytoprotective processes that may limit permanent damage. To investigate the biological significance of low-dose exposures, human lymphoblastoid cells were treated with alkylating agents that have different mechanisms of action and DNA targets: methylmethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 38 publications
10
157
5
1
Order By: Relevance
“…AUC measurement in blood, e.g., by Hb adduct measurements, bypass the problems of species-and high-to-low dose differences in metabolism of reactive compounds/intermediates. Deviations from linearity in dose-response due to DNA repair, etc., at very low exposure levels could exist for certain compounds (48). These are, however, not detected with the sensitivity in the standard test systems.…”
Section: Discussionmentioning
confidence: 94%
“…AUC measurement in blood, e.g., by Hb adduct measurements, bypass the problems of species-and high-to-low dose differences in metabolism of reactive compounds/intermediates. Deviations from linearity in dose-response due to DNA repair, etc., at very low exposure levels could exist for certain compounds (48). These are, however, not detected with the sensitivity in the standard test systems.…”
Section: Discussionmentioning
confidence: 94%
“…Datasets were identified that included a suitable number of replicates (preferably three or more), with a suitable number of cells/targets (e.g., mostly >10,000 cells analyzed per dose for the analysis of MN) and with several doses resulting in genotoxic event frequencies similar to the NOGEL and solvent control. In fact, the in vitro micronucleus datasets from Doak et al [2007] had several additional replicates at four doses surrounding the NOGEL, in order to reach 10,000 or more cells at this critical region, while LeBaron et al [2008] evaluated >10,000 cells per replicate. Experimental datasets that fit these requirements were very limited and are presented in Tables I and II.…”
Section: No-observed-genotoxic-e¡ect-levelmentioning
confidence: 99%
“…A Duplex 1-modified electrode (containing all normal DNA bases and no uracil) was first exposed to MMS, a known carcinogenic chemical [56]. During the reaction, MMS would methylate some of the DNA bases.…”
Section: Detection Of Chemical-induced Ap Sitesmentioning
confidence: 99%